Effect of various micro-porous layer preparation methods on the performance of a proton exchange membrane fuel cell. (1st January 2014) - Chen, Wei-Hung; Ko, Tse-Hao; Cheng, Su-I; Hung, Chih-Jung; Liang, Heng-Chia; Lin, Jui-Hsiang; Liu, Ching-Han
Proton exchange membrane fuel cells (PEMFCs) have been widely studied and discussed in the field of energy owing to their high energy efficiency and low waste emissions. A PEMFC uses hydrogen gas as a fuel, and works by causing hydrogen ions to link up with oxygen, producing liquid water as its sole by-product. The design of a PEMFC's micro-porous layer (MPL) can not only enhance cell performance, but also achieve better water management in a PEMFC system. In this paper, we examine the effects of spray and scrape MPL preparation methods on PEMFC performance. Our experimental results indicated that application of an MPL using the spray method yields better fuel cell performance. Furthermore, scanning electron microscopy (SEM) images reveal that the spray method produces pores with smoother surfaces and achieves a more uniform pore distribution. When the carbon black composition was 3 wt%, the current density of cells with MPL produced using the spray method reached 1210 mAcm –2 at a cell voltage of 0.5 V.